Richness of the Orchidaceae family in a cloud forest of Chocamán, Veracruz, Mexico - Tejeda-Sartorius, Olga; Téllez Velasco, María de los Ángeles Aída (Instituto de Ecología, A.C., 2017)
Background and Aims: Some fragments of cloud forest (CF) in central Veracruz have not been studied floristically. The aim of the present investigation was to record the richness of orchids in a fragment of this type of forest in Chocamán, Veracruz.Methods: Specimens were collected and scientific collections and bibliographic information were revised.Key results: The list included 36 species, belonging to 25 genera. Epidendrum was the genus with more species (7), followed by Dichaea, Lycaste, Oncidium, Prosthechea and Stelis, with two each one, and all other genera were represented by one species. Four species are endemic to Mexico (Epidendrum longipetalum, Gongora galeata, Oncidium incurvum and Trichocentrum pachyphyllum); and two are protected by the Mexican legislation (O. incurvum and Stanhopea oculata). Epidendrum magnoliae and Epidendrum cf. radioferens are new records for the Veracruz flora.Conclusions: The orchid flora studied here faces problems because of the land-use change and illegal extraction for trade, thus conservation measures are urgent.